IMPLEMENTATION OF THE PROBLEM-BASED LEARNING MODEL ASSISTED BY ARSO MEDIA WITH LOCAL WISDOM NUANCES - Maulida, Nur Khilya; Rachmawati, Aisyah; Sutarno, Sutarno; Mawarsari, Venissa Dian; Suprayitno, Iswahyudi Joko (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Students' problem-solving skills in solving social arithmetic are still experiencing difficulties, namely in terms of identifying problems, designing solutions in applying the right concepts and there are still errors in reasoning. In addition, in the current learning proces, it is necessary to utilize technology to motivate students to learn, but the media that has been applied so far has not been able to adjust to the needs of students. The existence of these problem requires a learning model assisted by media with nuances of local wisdom to be able to practice problem-solving skills. So this study aims to determine the implementation of the PBL model assisted by Arso media with nuances of local wisdom to improve mathematical problem-solving skills. This research is an experimental research in one of the private MTs in Bandungan. The data collection technique uses mathematical problem-solving ability test (pretest and posttest). Based on the mathematical problem-solving ability test, the average pretest score of 47.38 and posttest 80.66 and the n-gain value of 0.6163 with medium criteria were obtained, so it was stated that Arso media with nuances of local wisdom with PBL model can improve students mathematical problem-solving ability with moderate criteria.